The predictive power of the left-right self-placement scale for the policy positions of voters and parties. Issue 2 (4th March 2017) - Lesschaeve, Christophe
Abstract: The left-right self-placement scale is often used in political science as a proxy for the policy positions of voters and parties. Yet studies have suggested that, for voters, this relation is dependent on education level. These studies were, however, hampered by data limitations and restricted statistical analyses. In addition, the extent to which the relation between the left-right self-placement scale and policy positions differs for parties and voters has not been explored. This article looks at the differential relation between left-right self-placement and policy positions for voters with different education levels on an integrated dataset containing over 50 voter and party policy positions. It is found that the left-right self-placement scale is a much better predictor for the policy positions of parties than it is for the policy preferences of voters. Robustness checks show that neither the saliency of the policy positions nor their complexity moderates these findings.